A questionnaire-based qualitative study of therapist views on computerized CBT. (17th August 2016) - Newton, J.; Sundin, E. C.
Abstract: Few studies have explored therapists' views on computerized cognitive behavioural therapy (cCBT) and this study aimed to provide an in-depth understanding of accredited therapists' views on cCBT's role in treating depression. Twelve therapists constituted this self-selected sample (eight female, four male). Mean age was 52 years (range 46–61). The data obtained from a semi-structured questionnaire were analysed using thematic analysis. Three themes were identified and discussed: (1) the standardized nature of cCBT for depression, (2) the importance of the therapeutic relationship in cCBT, and (3) the pros and cons with cCBT as an alternative to CBT. The therapists in this study emphasized that innovations in CBT delivery formats (e.g. internet-based, computerized) show promise. However, participants expressed some views that clash with the evidence-based viewpoint. More work is needed to improve the implementation of evidence-based practice and policy.